2001
DOI: 10.1021/ac010799c
|View full text |Cite
|
Sign up to set email alerts
|

Chromogenic Lariat Ethers for Selective Alkali Metal Cation Recognition

Abstract: Twelve new proton-ionizable, picrylamino-type chromogenic lariat ethers derived from dibenzo-14-crown-4, dibenzo-16-crown-5 and dibenzo-19-crown-6 demonstrate good selectivity and remarkable color response upon extraction of alkali metal cations from basic aqueous solutions into chloroform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…Thus, the development of novel extractants, which perform better than conventional commercial extractants, is required for effective removal of toxic metal ions. For example, macrocyclic ligands such as crown ethers [6][7][8][9] and calixarenes [10][11][12][13] are known to exhibit specific interactions with Pb(II) because of the size fitting effect. However, these methods are time-consuming and expensive for large-scale application.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the development of novel extractants, which perform better than conventional commercial extractants, is required for effective removal of toxic metal ions. For example, macrocyclic ligands such as crown ethers [6][7][8][9] and calixarenes [10][11][12][13] are known to exhibit specific interactions with Pb(II) because of the size fitting effect. However, these methods are time-consuming and expensive for large-scale application.…”
Section: Introductionmentioning
confidence: 99%
“…Bartsch and co-workers showed that a calix [4]arene bearing N(X)sulfonylcarboxamide exhibits a good extraction selectivity for Hg 2 + and Pb 2 + over alkali and transition-metal ions. [13] A calix [4]arene (2) with two dansyl groups as part of the N(X)sulfonylcarboxamide (Calix-DANS2) was used for selective Hg 2 + extraction in acidic solutions in the millimolar concentration range, [14] but no attention was paid to the possible detection of Hg 2 + at low concentration. In a preceding paper, we reported preliminary results on the synthesis and the photophysical properties of a new calixarene Calix-DANS4 (3) bearing four dansyl groups which has been designed for the sensitive and selective detection of Pb 2 + .…”
Section: Introductionmentioning
confidence: 99%
“…6,9 A qualitative measure of acidity for proton-ionizable ligands is pH 0.5 , the aqueous phase pH at which half of the maximal metal ion loading is reached. 15 For lariat ether carboxylic acids 6, 7, and 19, the same pH 0.5 value of 7.0 was observed. Thus structural variation of the geminal aryl group from 1-naphthyl to 2-naphthyl to 9-phenanthryl in the sym-(aryl)dibenzo-16-crown-5-oxyacetic acid extractants did not influence the ligand acidity.…”
Section: Competitive Solvent Extraction Of Alkali Metal Ionsmentioning
confidence: 59%